A facile synthesis of novel near-infrared pyrrolopyrrole aza-BODIPY luminogens with aggregation-enhanced emission characteristics. Issue 59 (11th July 2017) - Li, Lanqing; Wang, Lingyun; Tang, Hao; Cao, Derong
Abstract : Two novel near-infrared pyrrolopyrrole aza-BODIPY luminogens (PPAB-2 andPPAB-3 ) with aggregation-enhanced emission characteristics were conveniently synthesized. Abstract : Here we report the facile synthesis of two triphenylethylene-modified pyrrolopyrrole aza-BODIPY dyes with an aggregation-enhanced emission feature. NIR-emitting nanoparticles with remarkable photostability properties and applications in bioimaging were generated due to their good dispersity in water and biocompatibility.